STRATEGI PEMASARAN JASA PENDIDIKAN (ANALISIS PENGEMBANGAN MADRASAH) - Mgs. Nazarudin (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2016)
The existence of Islamic School in the context of national education had not shown to the quality expected in every province there were Islamic schools (State) were built and managed specifically to be a superior Islamic schools. But other Islamic schools that were not built and managed specifically still cannot compete optimally. A form of competition was the quality, integrity, credibility and accountability in the eyes of the community and parents. Islamic schools were still viewed as